The causal effect of wrong-hand drive vehicles on road safety - Felix Roesel (Technische Universität Dresden, Center of Public and International Economics (CEPIE), 2017)
Left-hand drive (LHD) vehicles share higher road accident risks under left-hand traffic because of blind spot areas. Due to low import prices, the number of wrong-hand drive vehicles skyrockets in emerging countries like Georgia, Kyrgyzstan and Russia. I identify the causal effect of wrong-hand drive vehicles on road safety employing a new version" of the synthetic control method. Sweden switched from left-hand to right-hand traffcin 1967. Before 1967, however, almost all Swedish vehicles were LHD for reasons of international trade and Swedish customer demand. I match on accident figures in the period after 1967, when both Sweden and other European countries drove on the right and used LHD vehicles. Results show that right-hand traffic decreased road fatality, injury and accident risk in Sweden by a proximately 30 percent. An earlier switch would have saved more than 4,000 lives between 1953 and 1966.
urn:nbn:de:bsz:14-qucosa-229840
Keywords: R41; K32; C53; 330; road accidents; Sweden; natural experiment; synthetic control method